2018
DOI: 10.4172/2161-1017.1000292
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Yoga on Anthropometric and Physical Assessments in Adolescent Obesity

Abstract: Background: Adolescent Obesity is causing serious public health concern and in many countries threatening the viability of basic health care delivery. Many co-morbid conditions are seen in association with adolescent obesity. Interventions based on Yoga principles are found to have effective solutions for adolescent obesity. Aim: To evaluate the effect of the Yoga based intervention on anthropometric and physical assessments in Adolescent Obesity. Methods: RCT (Randomized Controlled Trial) was conducted on 53 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 13 publications
(13 reference statements)
0
2
0
5
Order By: Relevance
“…Similarly, Lison et al demonstrated positive impact of home based exercise in fat mass and waist circumference reduction (19). Yoga intervention was also shown to signicantly reduce weight, BMI, hip circumference and fat percentage in a randomized controlled trial study by Rathi et al (20). The positive benets of exercise and aerobics on obese children and adolescents have also been reported in several other studies as well (21) (22).…”
Section: Discussionmentioning
confidence: 73%
“…Similarly, Lison et al demonstrated positive impact of home based exercise in fat mass and waist circumference reduction (19). Yoga intervention was also shown to signicantly reduce weight, BMI, hip circumference and fat percentage in a randomized controlled trial study by Rathi et al (20). The positive benets of exercise and aerobics on obese children and adolescents have also been reported in several other studies as well (21) (22).…”
Section: Discussionmentioning
confidence: 73%
“…Çocuklar için yapılan fiziksel uygunluk ölçümleri, çocukların bedenlerine yönelik olumlu tutum geliştirmelerini sağlarken, fiziksel durumları hakkında bilgi edinmelerine de yardımcı olur. El kavrama kuvveti, dikey sıçrama, otur-uzan testi, mekik çekme, barfiks ve flamingo denge testi gibi değerlendirmelerin yer aldığı EUROFİT testlerinden mekik ve flamingo denge testi adolesan obezitesinin değerlendirilmesinde oldukça önemlidir [10]. Çocukluk çağı obezitesi sadece endokrin, gastrointestinal, muskuloskeletal, pulmoner ve kardiyovasküler sistem için değil vücuttaki hemen her sistemi olumsuz etkileyen komorbiditeler ile ilişkilidir [9].…”
Section: Obezitenin Değerlendirilmesiunclassified
“…Ergenlik döneminde, fiziksel aktivitenin tek başına obezitenin sebeplerini ortadan kaldırması pek de mümkün değildir. Çünkü fiziksel aktivite eksikliği, genetik, hareketsiz yaşam gibi durumların yanısıra benlik saygısının düşük olması, başarı kaygısı, depresyon gibi psikolojik sebepler de azımsanamayacak kadar fazladır [10]. Yoganın geleneksel amaçları vücut ile zihni birleştirmek, alışkanlıklar ve biliş üzerinde etki oluşturmak, mutluluk ve iyilik halini sağlamaktır [10,36].…”
Section: Yogaunclassified
See 2 more Smart Citations